نمذجة ومحاكاة طرق تنظيم سرعة دوران المحركات التحريضية ثلاثية الطور - غدير, نسرين (Latakia University Journal -Engineering Sciences Series, 2017)
تعتبر المحركات التحريضية أكثر أنواع الآلات الكهربائية انتشارا و استخداما وفي شتى المجالات و المنشآت الصناعية و المنزلية بسبب موثوقيتها العالية، وتكلفتها المنخفضة ومتانتها. ومع ذلك، المحركات التحريضية ليس لديها أصلا القدرة على عملية تغير السرعة. ونتيجة لهذا السبب سابقا كانت محركات التيار المستمر DCهي الأكثر استخداما في معظم المحركات الكهربائية. ولكن أدت التطورات الأخيرة في طرق التحكم في المحركات التحريضية لاستخدامها على نطاق واسع في كافة المجالات.يوجد عدة طرق لتنظيم سرعة دوران المحركات التحريضية منها تغيير عدد أقطاب المحرك، تغيير تردد المنبع المطبق على المحرك، تغيير مقاومة الدائر، تغيير قيمة التوتر المطبق على ملف الثابت، طريقةConst)= (V/F.تعتبر طريقة Const)= (V/Fمنأكثر الطرق شيوعا و استخداما. في هذه الطريقة تبقى النسبة V/F ثابتة التي عندها يتولد سيالة مغناطيسية ثابتة و عندها العزم الأعظمي لا يتغير. في هذه الطريقة إن المحرك يستخدم بشكل كامل و فعال.Induction motors are the most widely used electrical motors due to their reliability, low cost and robustness. However, induction motors do not inherently have the capability of variable speed operation. Due to this reason, earlier dc motors were applied in most of the electrical drives. But the recent developments in speed control methods of the induction motor have led to their large scale use in almost all electrical drives.Out of the several methods of speed control of an induction such as pole changing, frequency variation, variable rotor resistance, variable stator voltage, constant V/f control, slip recovery method etc, the closed loop constant V/f speed control method is most widely used. In this method, the V/f ratio is kept constant which in turn maintains the magnetizing flux constant so that the maximum torque remains unchanged. Thus, the motor is completely utilized in this method.